Learning From Investigation After Death. (August 2018) - Griffiths, Benedict T.; Sebire, Neil J.; Brierley, Joe
Abstract : Objectives: The acceptability of traditional postmortem examination to bereaved families, coupled with a misguided professional view about their limited utility, has led to decrease in this ultimate investigation. Research recurrently demonstrates that postmortem examination provides clinically relevant information despite ever-improving diagnostic techniques. This review examines postmortem examination for children who die in PICU—whether consented or nonconsented (legally mandated). It explores how such investigations might provide useful information and suggests that PICU and pathology teams work together to provide information for bereaved families to either enable them to consent to postmortem interventions or understand necessary forensic processes. Newer technologies such as postmortem imaging and laparoscope-assisted/ultrasound-guided tissue sampling are reviewed, with the hope that greater acceptability to families may lead to a welcome resurgence in postmortem information for clinicians, tempered by realization that widespread acceptance of their equivalence to standard techniques by most forensic services is awaited. Data Sources: Literature review. Study Selection: Journal articles describing practices in pediatric and adult postmortem examination. Data Extraction: Not available. Data Synthesis: Not available. Conclusions: The PICU team have a duty to help bereaved parents understand what postmortem investigations are available, or might be mandated, after the death of their child. A thoughtful, unhurried, and compassionate discussion should be arranged with expert pathology teams and any specialists who have cared for the child to explain how investigations can provide information about what is involved—including availability and suitability of newer techniques. This should include information about when a child's body, organs, or tissues will be available for the funeral, necessary legal procedures and how and when results will be explained to them.